Aging sensitizes male mice to cognitive dysfunction induced by central HIV-1 gp120 - Sparkman, Nathan L. (Exp Gerontol, 2019)
Although highly active antiretroviral therapy has lead to improved prognosis and alleviation of some HIV-related disease complications, it has not provided complete protection against HIV-associated dementia. As the population of persons living with HIV grows older and aged persons represent a significant number of new infections, it is important to understand how HIV may affect the aged brain. In the current study, both adult and aged mice were treated with HIV gp120 and trained in a reference memory version of the water maze. Analysis of probe data revealed that aged animals treated with gp120 demonstrated profound decrements in water maze performance compared to gp120 treated young animals and saline treated aged or young animals. Additionally, we examined the neuroinflammatory responses in the aged and adult brain 4 h after treatment with gp120. Pro-inflammatory cytokines associated with neuroinflammation are known to be antagonistic to learning and memory processes and aged and adult animals treated with gp120 demonstrated similar increases in IL-1 β and IL-6 in the hippocampus and cortex. Additionally, gp120 treatment was associated with an increase in MHCII gene expression, a marker of microglial activation, in the hippocampus. Although, the aged brain demonstrated a similar inflammatory profile at the time point measured, aged animals were more sensitive to cognitive dysfunction related to gp120 treatment. This finding supports the theory that aging may be a significant risk factor in the development of HIV-associated dementia.